Collective Integrations of Christianity and Sexual and Gender Diversity: Ethnography of “Rainbow Communities” in Spain - Barrera-Blanco, José (2025)
This article uses ethnography to explore some of the ways in which religion and sexual diversity intersect in contemporary society. It studies the case of the so-called “rainbow communities” in Spain: groups of Christian lesbians, gays, bisexuals, and trans individuals (LGBT+) who organize themselves to live these identities complementarily against the frequent oppositional understandings. The research analyzes data collected during continuous fieldwork with these communities from 2019 to 2023, and through a systematic review of archives. First, it traces the historical path of these communities, situating their development within broader processes of religious transformation, activist progress, and the social and legal recognition of diversity. Second, it assesses how they impact on the Christian field by offering a pastoral care model based on pluralism that addresses the population’s vital and spiritual needs unmet by mainstream religious institutions. Finally, it argues how their sociability rooted in Christian and LGBT+ activist values produces a context conducive to practising and developing identity in an integrated way.